THE PSYCHOLOGY OF CONTENTMENT: Said Nursi’s Al-lama‘at as A Framework for Sufi Behavioral Economics - Moch. Hoerul Gunawan; Muhamad Faiz Al Afify; Mohammad Yahdi; Caca Handika; Habibi (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This paper examines al-Lama‘at by Said Nursi as a conceptual foundation for the development of Sufistic Behavioral Economics. In contrast to mainstream behavioral economics, which emphasizes cognitive biases, decision heuristics, and bounded rationality, Nursi offers a spiritual-psychological perspective rooted in Qur’anic ethics. The concepts of qana‘ah (contentment), zuhd (detachment from material possessions), and ridha (acceptance) are understood as moral frameworks that shift economic behavior from the pursuit of material utility toward inner satisfaction and spiritual purification. From this perspective, economic decisions reflect an individual’s spiritual condition, value orientation, and moral awareness. Through a hermeneutic analysis of al-Lama‘at, this study formulates a triadic model of “inner-contentment economics” that explains the role of spiritual consciousness in shaping consumption patterns, saving behavior, and attitudes toward risk and uncertainty. By integrating spirituality, psychology, and economic behavior, this study offers a critical alternative to dominant economic paradigms and underscores the centrality of moral objectives in human economic activity.